2019
DOI: 10.1017/s2045796019000313
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of suicide attempts in individuals with schizophrenia: a meta-analysis of observational studies

Abstract: Aims Suicide attempt is an important indicator of suicide and potential future mortality. However, the prevalence of suicide attempts has been inconsistent across studies. This meta-analysis aimed to examine the prevalence of suicide attempts in individuals with schizophrenia and associated correlates. Methods Relevant publications in Embase, PsycINFO, PubMed, Web of science and Cochrane were systematically searched. Data on the prevalence of suicide attempts in individuals with schizoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
35
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 62 publications
7
35
3
Order By: Relevance
“…Various studies on different factors associated with suicide in schizophrenia patients, such as age, gender, age of onset of illness and duration of illness yielded conflicting results. 7,8,36,[45][46][47] Our findings found no association between age, gender, marital status, age of onset of illness and duration of illness with suicidality in schizophrenia inpatients, which has been reported in previous studies. 26,38 Earlier studies showed that suicidal risk in schizophrenia patients peaked during the first week of hospitalization and during the first week after discharge.…”
supporting
confidence: 50%
“…Various studies on different factors associated with suicide in schizophrenia patients, such as age, gender, age of onset of illness and duration of illness yielded conflicting results. 7,8,36,[45][46][47] Our findings found no association between age, gender, marital status, age of onset of illness and duration of illness with suicidality in schizophrenia inpatients, which has been reported in previous studies. 26,38 Earlier studies showed that suicidal risk in schizophrenia patients peaked during the first week of hospitalization and during the first week after discharge.…”
supporting
confidence: 50%
“…Moreover about one quarter of patients with bipolar disorder have a seasonal pattern of their depressive recurrences, and one out of six patients present with seasonal manic recurrences (32,33). Patients with schizophrenia are up to 20 times more likely to die by suicide than the general population use (34). A particular shared vulnerability between suicidal behaviors and psychiatric disorders has been con rmed in our study.…”
Section: Discussionsupporting
confidence: 73%
“…Diagnostic and Statistical Manual of Mental Disorders, third edition (DSM-III), DSM-IV, and the Tenth Revision of the International Statistical Classification of Diseases and Related Health Problems (ICD-10)); Intervention ( I ): not applicable; Comparison ( C ): not applicable; Outcome ( O ): prevalence of SI and/or SP or relevant data that enabled calculations of the prevalence of SI/SP; Study design ( S ): cross-sectional or cohort studies (only the baseline data of cohort studies were extracted). Exclusion criteria included: (1) timeframe of prevalence of SI and/or SP was missing; (2) studies published in non-English; (3) in order to increase homogeneity [ 17 ], studies with mixed samples (e.g. schizoaffective or schizophrenia spectrum disorders) in which data on schizophrenia cannot be extracted were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…In order to develop and adopt effective measures and public education to reduce suicide risk and relevant negative health outcomes, exploring the epidemiology of suicidality in people living with schizophrenia is of great public health significance. A meta-analysis [ 17 ] showed the pooled lifetime prevalence of SA was 26.8% (95% CI: 22.1−31.9%) among people living with schizophrenia. In contrast, no meta-analysis was published for pooled SI, and the estimates within individual studies [ 18 23 ] ranging between 11.0% in China [ 23 ] and 51.4% in the USA [ 21 ].…”
Section: Introductionmentioning
confidence: 99%